Teacher Education for Preschool Education during the Era of the Military Dictatorship - Ana Maria Orlandina Tancredi Carvalho (Universidade Federal do Rio Grande do Sul, 2015)
This article analyzes teacher formation for pre-school education in the period of the military dictatorship. I have conducted our research in Revista Criança, an official publication of the Ministry of Education, first national journal for this field. Our bibliographical and document research took place from 2003 to 2006 - period of my PhD, taking as the base for this research: legislation, documents, interviews and the Magazine itself, published between 1982 and 1985. Fourteen magazines served as basis for this education policy within that period, supported on the Theory of Human Capital, which, in the education field, is expressed through technicist pedagogy. The magazine does not question the prejudice against the poor people nor the authoritarianism and anticipates the education for children in pre-school education.